Factors Affecting The Interaction Between The Population of Lakkang Island And The Activity Center - Yanti, Suci Anugrah; Zahirah, Andi Nada; Patandianan, Marly Valenti; Arifin, Mimi (Faculty of Engineering, Andi Djemma University, 2026)
Population movement is inseparable from interactions from the origin area to the destination location. This population movement is also influenced by the presence of push factors. Interaction is not only determined by physical distance, but also by social, economic, and accessibility factors. The condition of Lakkang Island has limitations in geography. The residents of Lakkang Island have high mobility to areas outside the island which has its own challenges. This study aims to analyze the factors that influence population interaction with activity centers. The sampling technique used is non-probability sampling. The method used is purposive sampling of 122 respondents. Data collection techniques are carried out by distributing questionnaires and interviews. The analysis technique is carried out through descriptive analysis and multiple regression analysis using R Studio tools. The results show that economic factors (X2) are the main contributors that strengthen the interaction of settlements with activity centers, especially in the economic dimension with a coefficient value = +0.2637; p = 0.0001. The social factor (X3) has a significant but negative influence on the social (coefficient = -0.1198; p = 0.0378) and physical (coefficient = -0.0777; p = 0.0384) dimensions. This indicates that the stronger the internal social cohesion, the smaller the physical and social dependence on external factors. The accessibility factor (X1) is only significant on the economic dimension and even shows a negative direction (coefficient = -0.0994; p = 0.0219). The economic factor is the most dominant factor influencing population interaction with activity centers. This means that increasing physical connectivity without increasing local capacity can lead to outflows (economic and social), rather than two-way integration. Therefore, the economic factor is important to support regional integration.